Provenance of African-Born Individuals from the Colonial Cemetery of Campeche (Mexico) by Means of Trace Elements Analysis - Andrea Cucina; Hector Neff; Vera Tiesler (Dental Anthropology Association, 2004)
The present study investigates the issue of foreign provenance of African individuals buried in the early colonial cemetery of Campeche (Mexico) using multiple trace elements analysis from the first permanent molar. It rests on the assumption that, like for Strontium isotopes, the elemental pattern in the first molar reflects the hydro-geological environment the individual grew in. The individuals of African ethnicity were identified from their pattern of dental morphology. Twenty-eight individuals were analyzed in this context, eight of them supposedly Africans, while 15 were infants or early juveniles and five from the prehispanic site of Xcambó in northern Yucatán. The infants and juveniles were likely born in the area, thus serving as term of comparison for the |local" elemental pattern. The elements' ppm concentrations of the 28 individuals were elaborated using Principal Components Analysis. Results tend to cluster the infants and some of the African individuals together, though the majority of the Africans tend to group. One African individual in particular separates well from all the others. Assuming that dietary components might interfere with the individuals' distribution, only elements not related to diet were thus used, without different results from the previous analysis. Indeed, the elements correlating high with the first two components are non-dietary. Trace elements patterns indicate that some of the African individuals interred in the early colonial cemetery might have been born in other places, though we cannot infer on their place of origin, while others were probably born in the New World.